Morphological description of Mepraia spp. females (Hemiptera: Reduviidae, Triatominae) - Lasserre, Daniel Frías; de Oliveira, Jader [UNESP]; Pinotti, Heloisa [UNESP]; da Rosa, João Aristeu [UNESP] (Elsevier, 2019)
Mepraia spinolai, M. gajardoi and M. parapatrica occur in distinct regions in Chile. The females of the three species are micropterous. The males of M. gajardoi are brachypterous, those of M. parapatrica can be brachypterous or macropterous and those of M. spinolai can be micropterous, brachypterous or macropterous. Morphological studies were carried out by scanning electron microscopy of female specimens collected in the wild. Head, thorax and abdomen characters of the three species there were not previously studied by SEM allowed a clear distinction amongst the three species.
Keywords: Brachypterous; Female; Identification; Micropterous; Morphology; SEM